Implementasi Pendidikan Agama Pada Anak Usia Dini: Studi Kasus PAUD Sehati Kebayan Brang Biji Sumbawa Besar - Muji Agus Sofiyandi (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
Sehati Kebayan Early Childhood Education (PAUD), Brang Biji Village, Sumbawa Besar is a school that has students from various religions, including; Islam, Christianity and Catholicism. In developing religious aspects, this school emphasizes 2 (two) religious dimensions, namely, firstly, it is very important for young children to be introduced to religion so that children internalize religious values in worship. Second, children are instilled with the attitude of religious tolerance from an early age so that children are accustomed to the attitude of tolerance among their friends even though they have different religions. Based on this brief background, the researcher focused on the research, namely how is the implementation of religious education for early childhood at PAUD Sehati Kebayan Kelahan Brang Biji? This research uses a qualitative research method approach which is directed at field research. The subjects in this research were Islamic, Christian and Catholic religious teachers. Meanwhile, the object of this research is strategies for developing religious worship and religious tolerance. Using interview, observation and documentation techniques. The validity of the data is measured using method and source triangulation techniques. Data analysis was carried out using data reduction steps, data presentation, and drawing conclusions. The results of research on the implementation of religious education in early childhood include 3 (three) implementation activities of religious education, namely 1) routine learning activities, including; praying together with different prayer methods/attitudes but the content of the prayer is general and uses Indonesian, English and Mandarin, 2) integrated learning activities, including; activities to develop cognitive, physical motor, language and arts aspects that are integrated with the development of religious values, and 3) special learning activities, including; faith, prayers/ways of worship, prayers, reading and understanding religious books, religious songs or praises, introducing fasting and introducing days of worship or commemoration days of each religion.